Legal Protection for Appearers when the Notary's Existence is Unknown (Lost Contact) - Yusti Merilistia; Istislam; Yenny Eta Widyanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research examines the legal protection of clients when the notary's wherea-bouts are unknown (lost contact).describe and analyze the certainty of legal protection for appearers who are harmed by a notary whose whereabouts are unknown (lost contact) and to analyze and formulate forms of legal protection that can guarantee legal certainty for ap-pearers who are harmed by a notary whose whereabouts are unknown (lost contact).This research is a normative juridical research through literature studyusing statutory approach (statute approach) and conceptual approach (conceptual approach). The main issues were analyzed using primary legal materials includingProvisions of Article 463 in conjunction with Article 467 of the Civil Code, provisions of Article 15, Article 16, Article 17, Article 62, Article 63 Article 67, Article 69 and Article 70 of Law Number 30 of 2004 concerning the Position of Notary Public juncto Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary, Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 15 of 2020 concerning Procedures for Examining the Supervisory Board of Notaries and Notary Code of Ethics. Legal materials were analyzed based on prescriptive analysis and grammatical and systematic interpretation techniques. Based on the research results it is known thatLegal protection for appearers who are harmed by a notary whose whereabouts are unknown (lost contact) based on the analysis of UUJN Amendment) is weak, because basically (“UUJN”) juncto (“UUJN”) Amendment has accommodated arrangements regarding the presence of a notary in the exercise of his office. No matter of how, there are incomplete norms in regulating the absence of a notary in Law Number 2 of 2014 concerning Notary office (“UUJN”) juncto (“UUJN”) Amend-ment because it cannot accommodate the existence of a notary whose whereabouts are un-known (lost contact), including not being able to guarantee legal protection to appearers who are disadvantaged because the event of absence of a notary is not contained in the provisions in UUJN juncto UUJN Amendment which is used as a guideline results in legal uncertainty which causes legal protection for aggrieved appearers to be also not guaranteed